2013
DOI: 10.15625/1859-3097/13/1/3503
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Distribution of Sharks in Quy Nhon Bay and Neighboring Waters

Abstract: TÓM TẮTPhân tích 52 mẫu vật được thu thập và mô tả trong thời gian từ tháng 2/2010 đến tháng 12/2012 đã cho phép xác định 12 loài, thuộc 6 giống, 5 họ, 3 bộ cá nhám/mập ở vùng biển Quy Nhơn và lân cận, trong đó bộ cá mập mắt trắng (Carcharhiformes) có số loài nhiều nhất (7 loài) sau đó là bộ cá nhám thu (Lamniformes) với 3 loài. Bộ cá nhám góc (Squaliformes) và bộ cá nhám râu (Orectolobiformes) mỗi bộ 1 loài. Về phân bố, bước đầu có thể cho rằng cá nhám voi (Rhincodon typus), cá nhám đuôi dài mõm ngắn (Alopias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…8E). It has been previously misidentified with S. japonicus in Vietnam as seen in Quang et al (2013). It inhabits continental slopes between 360-525 m depth (Zhu et al 1984; present study).…”
Section: Squalus Acutirostris Zhu Meng and LI 1984mentioning
confidence: 66%
See 1 more Smart Citation
“…8E). It has been previously misidentified with S. japonicus in Vietnam as seen in Quang et al (2013). It inhabits continental slopes between 360-525 m depth (Zhu et al 1984; present study).…”
Section: Squalus Acutirostris Zhu Meng and LI 1984mentioning
confidence: 66%
“…Squalus japonicus has been misidentified in waters outside Japan (e.g. Vietnam by Quang et al 2013) and many morphological variations were reported earlier in Compagno et al (2005b) and Last et al (2007b) for material from Indonesia, Philippines and Western Australia, compromising the correct application of this nominal species. To clarify the taxonomic status of S. japonicus across the Western Pacific Ocean, the designation of a neotype along with a re-description of this species is provided herein.…”
Section: Geographical Distributionmentioning
confidence: 97%